Hubungan Antara Stress Psikososial, Sedentary Lifestyle, Asupan Karbohidrat dengan Status Gizi Remaja SMK di Wilayah Kecamatan Tuban - Gitta Maulani; Miftahul Munir; Dian Ayu Ainun Nafies (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The underlying problem of this study is the high incidence of nutritional problems, such as under- or over-nutrition, in adolescents due to greater nutritional requirements during growth. Research Objectives: This study examines the relationship between psychosocial stress, sedentary lifestyle, carbohydrate intake, and nutritional status in adolescents. Research Methods: Using a cross-sectional analytic research method on 284 out of 984 adolescent population, this study analyzed the data with Spearman correlation test. Results: The results showed a significant association between the three independent variables (psychosocial stress, sedentary lifestyle, and carbohydrate intake) and the dependent variable (nutritional status). Each independent variable had a significant p-value: 0.057 for psychosocial stress, 0.592 for sedentary lifestyle, and 0.054 for carbohydrate intake. Conclusion: This study concludes that there is a significant relationship between psychosocial stress, sedentary lifestyle, and carbohydrate intake with adolescent nutritional status. Therefore, it is recommended that adolescents apply a balanced nutritional pattern in their daily lives.